Job Relevant Information on Government Managerial Performance: The Role of Affective Organizational Commitment - Febrianti, Andin Vivian; Rohma, Frida Fanani (Business Management Analysis Journal (BMAJ), 2023)
This study aims to investigate the moderating effect of affective organizational commitment on job-relevant information (JRI) on government managerial performance. The inconsistent results regarding the impact of JRI on government managerial performance lead to differences in perceptions of JRI functions. The inconsistency of the research results is possible due to phenomena that have yet to be caught in previous studies. Based on the goal-setting theory, this study captured the construct of affective organizational commitment. The research used a quantitative method using a survey of 56 Regional Government Organizations (RGO) with 180 respondents in Pasuruan Regency, East Java, Indonesia. The sampling method used judgment sampling, which obtained as many as 180 respondents. Testing the research hypothesis was carried out using SmartPLS 4.0. The study results show that job-relevant information encourages the government managerial performance of regional apparatus. The existence of affective organizational commitment impacts improving government managerial performance. Moreover, the findings of this study indicate that affective organizational commitment can strengthen JRI's influence on the government managerial performance of the local government apparatus. This research shows that the affective organizational commitment possessed by officials can encourage the influence of job-relevant information to improve the managerial performance of local government officials